1993
DOI: 10.1007/bf00237429
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of somatic embryogenesis and plant recovery in cassava

Abstract: Methods for improving the efficiency of plant recovery from somatic embryos of cassava (Manihot esculenta Crantz) were investigated by optimizing the maturation regime and incorporating a desiccation stage prior to inducing germination. Somatic embryos were induced from young leaf lobes of in vitro grown shoots of cassava on Murashige and Skoog medium with 2,4-dichlorophenoxy acetic acid. After 15 to 20 days of culture on induction medium, the somatic embryos were transferred to a hormone free medium supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
3
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 13 publications
4
26
3
3
Order By: Relevance
“…31 Desiccation also has been reported to promote somatic embryo differentiation and development to other crops like as soybean, 36,37 wheat, 38 spruce 39 and cassava. 40 In recent years tissue culture techniques are being used as a useful tool to elucidate the mechanism involved in salt tolerance. 41,42 Several metals are essential nutrients for plants, yet they become toxic at high levels and deleteriously affect crop yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…31 Desiccation also has been reported to promote somatic embryo differentiation and development to other crops like as soybean, 36,37 wheat, 38 spruce 39 and cassava. 40 In recent years tissue culture techniques are being used as a useful tool to elucidate the mechanism involved in salt tolerance. 41,42 Several metals are essential nutrients for plants, yet they become toxic at high levels and deleteriously affect crop yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the efficiency of somatic embryo maturation and plant conversion can be improved via the use of abscisic acid (ABA) which is known to synchronise embryo maturation (Groll et al 2002;Quainoo and Dwomon 2012), confer desiccation tolerance (Torres et al 2001) and enhance plant conversion (Quainoo and Dwomon 2012). Also, desiccation of somatic embryos prior to culture on standard cassava medium has been used to enhance plant conversion (Matthews et al 1993). The protocol described below aims to optimise cassava somatic embryo induction at both the primary and the cyclic stage using the synthetic auxins 2,4-D and picloram.…”
Section: Somatic Embryo Conversion Into Plantsmentioning
confidence: 99%
“…Partial desiccation has been reported to accelerate plant organogenesis or embryogenesis and results in high regeneration ability significantly in grape (Gray, 1989), wheat (Cheng et al, 2003), Brassica napus (Kott & Beversdorf, 1990), rice (Rance et al, 1994;Saharan et al, 2004;Tsukahara & Hirosawa, 1992) and cassava (Mathews et al, 1993). The possible mechanism about its promotion on plant regeneration capacity may be that partial desiccation terminates the developmental mode and "switches" the embryo into a germination mode (Attree et al, 1991).…”
Section: Partial Desiccationmentioning
confidence: 99%